KONDISI PERAIRAN TELUK BULI HALMAHERA TIMUR BERDASARKAN KOMPOSISI JENIS, KELIMPAHAN, DAN INDEKS-INDEKS BIOLOGI FITOPLANKTON - Ilyas, Yuliana Andi; Ahmad, Fasmi (Jurnal Harpodon Borneo, 2017)
The condition of Buli Bay waters is very important to know and needed to support the utilization and management of coastal and marine resources in these waters. Until now, information about the condition of Buli Bay waters is still very limited so this research becomes important. This research aims to assess the condition of the Buli Bay waters East Halmahera based on species composition, abundance, and phytoplankton biological indexes. The research was conducted in December 2014 in the waters of Buli Bay of East Halmahera Regency of North Maluku Province in 5 (five) stations. Sampling phytoplankton using filtration method by making the plankton withdrawal horizontally for 5 minutes. The results obtained 19 genera from two classes of phytoplankton namely Bacillariophyceae (10 genera) and Dinophyceae (9 genera). During the research, the biological index values of phytoplankton were: diversity index (H') : 1.4942-2.0940, equitability index (E) : 0.7415 - 0.9284, and dominance index (D) : 0.1454-0.2893. Conditions of Buli Bay waters based on the value of phytoplankton diversity index included in the category of waters with moderate fertility Key words : abundance, species composition, biology index, and Buli Bay